PEMAMFAATAN MEDIA SOSIAL MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Lina Purnamasari; Acmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The presence of social networking sites among the student has brough about a change in his life. One of them on social networking sites are bringing the student to more frequently communicate and exchange information. This study uses a quantitative approach to the descriptive type. Descriptrive type was chosen because the researchers intend to describe how the behavior of the utilization of social networking sites in Soceity Scince on University of Riau, without the reseacher to test hypotheses. Number of respondents researchers 50 people. Data were collected using questionnaires and interviews with some respondents who have been selected by the researcher to obtain answers as clearly as possible and the facts supporting the findings of this study. From the analysis of the data obtained, it can be in the know behavior in the use of social networking University of Riau, student are more likely to utilize these social networking sites are the female sex , they take advantage of this social networking site for students want more information up to date as well as the students want to add friends in cyberspace, of the respondents use these networking sites to socialize in a sense for communicating and sharing an your friends on social networking sites, becouse the social networking site is already provide a fitt.Key word : social networking , Behavior Utilization